Interface treatment using amorphous-carbon and its applications - Choi, Myung Sik (Sci Rep, 2020)
Breakthrough process technologies have been introduced that can increase the chemical sensitivity of an interface at which reactions occur without significantly altering the physico-chemical properties of the material. Such an interfacial treatment method is based on amorphous-carbon as a base so that fluids can be deposited, and the desired thickness and quality of the deposition can be ensured irrespective of the interface state of the material. In addition, side effects such as diffusion and decreasing strength at the interface can be avoided. This is simpler than existing vacuum-based deposition technology and it has an unmatched industrial advantage in terms of economics, speed, accuracy, reliability, accessibility, and convenience. In particular, this amorphous-carbon interface treatment technology has been demonstrated to improve gas-sensing characteristics of NO(2) at room temperature.